PERANCANGAN APLIKASI E-LEARNING UNTUK MENINGKATKAN EFISIENSI DAN EFEKTIVITAS PEMBELAJARAN DI SMK N BOJONGGEDE - Lolanda Hamim Annisa; Setiawan, M. Dendy; Alfariza, Rico; Fitro, Akhmad Angidanal; Zahrani, Salsa; Agustianingsih, Devany (LP3M Universitas Putra Bangsa, 2024)
Information technology is currently needed in various fields, including health, business and education. A real example of the use of information technology in the world of education is E-Learning. In fact, E-Learning is a form of conventional learning expressed in digital format via internet technology. SMK N BOJONGGEDE is a school whose teaching and learning activities still use conventional systems. This causes difficulties for students and teachers in accessing information from school subjects. In building this system using the PHP programming language with a MySQL database. The Waterfall method is used in system development and includes several steps such as system requirements analysis, system design, program code creation, testing, and implementation. The aim contained in this research is to create a Website-Based ELearning Application at SMK N BOJONGGEDE which is expected to help the school, especially teachers and students in the process of teaching and learning activities.